Daraz Bangladesh Limited is changing the online shopping experiences : the successful launch of fatafati friday - Uddin, Md. Minhaz (BRAC University, 2016)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2016.